Brachytherapy: An overview for clinicians. (30th July 2019) - Chargari, Cyrus; Deutsch, Eric; Blanchard, Pierre; Gouy, Sebastien; Martelli, Hélène; Guérin, Florent; Dumas, Isabelle; Bossi, Alberto; Morice, Philippe; Viswanathan, Akila N.; Haie‐Meder, Christine
Abstract: Brachytherapy is a specific form of radiotherapy consisting of the precise placement of radioactive sources directly into or next to the tumor. This technique is indicated for patients affected by various types of cancers. It is an optimal tool for delivering very high doses to the tumor focally while minimizing the probability of normal tissue complications. Physicians from a wide range of specialties may be involved in either the referral to or the placement of brachytherapy. Many patients require brachytherapy as either primary treatment or as part of their oncologic care. On the basis of high‐level evidence from randomized controlled trials, brachytherapy is mainly indicated: 1) as standard in combination with chemoradiation in patients with locally advanced cervical cancer; 2) in surgically treated patients with uterine endometrial cancer for decreasing the risk of vaginal vault recurrence; 3) in patients with high‐risk prostate cancer to perform dose escalation and improve progression‐free survival; and 4) in patients with breast cancer as adjuvant, accelerated partial breast irradiation or to boost the tumor bed. In this review, the authors discuss the clinical relevance of brachytherapy with a focus on indications, levels of evidence, and results in the overall context of radiation use for patients with cancer.